Serum Erythropoietin, Insulin-like Growth Factor 1, and Vascular Endothelial Growth Factor in Etiopathogenesis of Retinopathy of Prematurity - ÇERMAN, EREN; HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER; ŞAHİN, ÖZLEM (SLACK INC, 2013)
BACKGROUND AND OBJECTIVE: The role of growth factors in the pathogenesis of retinopathy of prematurity (ROP) is known. To better understand this issue, the authors investigated vascular endothelial growth factor (VEGF), insulin-like growth factor 1 (IGF-1), and erythropoietin (EPO) levels in the cord blood of premature newborns. PATIENTS AND METHODS: IGF-1, VEGF, and EPO levels were measured in cord blood samples obtained from 93 infants less than 32 weeks of gestational age at birth, and their predictive value in the development of ROP was investigated. RESULTS: The mean birth age and mean birth weight were 32.2 +/- 1.5 weeks and 1,678 +/- 326 g, respectively, in infants without ROP and 29.6 +/- 2.3 weeks and 1,384 +/- 343 g, respectively, in infants with ROP. Multivariate logistic regression analysis showed that only the gestational age and the serum VEGF at birth were independently associated with the risk of developing ROP (P = .002, Exp[B] = 0.514, CI = 95%: 0.341-0.775; P = .028, Exp[B] = 0.999, CI = 95%: 0.997-1.00). CONCLUSION: Serum VEGF levels at birth were lower in infants who later developed ROP. This may have a predictive value for ROP and contribute to the pathogenesis, because affected infants may be more susceptible to extrauterine hyperoxic insult.
Keywords: DIABETIC-RETINOPATHY; GESTATIONAL-AGE; BIRTH-WEIGHT; CORD-BLOOD; IGF-I; INFANTS; PLASMA; CANCER